Accountability policy in favor of trust in school institution and teachers? - Maroy, Christian (Swiss Journal of Educational Research, 2012)
Is the rise of accountability, external testing and evaluation in education related with a loss of trust from the State and users towards schools organizations? Does it mean a doubt about their capacity to achieve their goals and missions? Is it a symptom of a loss of trust in the teacher’s professionalism? We deal with these questions, on the base of theories of social trust. We distinguish on one hand the theories which focus on trust within economic transactions and on the other, the ones problematizing political trust of citizens towards institutions. We argue that accountability institutional arrangements aim to reduce customers or managers uncertainty about opportunism from professionals and school quality opacity. What is in stake is to facilitate the functioning of the «school market» or of the «school production system», with a risk of a loss of professional autonomy for teachers. These accountability arrangements do not guarantee that Schools become again a trustworthy political institution.